Eucalyptus shading and allelopathy in the germination and development of pitaya (Hylocereusundatus) - Pereira Ramos, Martha Cristina; Ferreira de Oliveira, Celismar; Rangel Junior, Ivan Marcos; Aparecida Rodrigues, Mariane; Salles Pio, Leila Aparecida; Sales Guimarães, Paulo Henrique (Comunicata Scientiae, 2022)
Eucalyptus spp. it is known to be part of most forests planted for commercial use in Brazil, however when intercropped with Pitaia (Hylocereus undatus), few studies report this interaction. The objective of this work was to evaluate the effects of shading and the existence of allelopathic interaction between Eucalyptus spp and pitaia (H. undatus) in the field, as well as the action of eucalyptus leaf extract in the germination of pitaia seeds in laboratory conditions. In the field experiment, the statistical model of randomized block design (DBC) was used, with the use of adult plants of pitaia and eucalyptus, evaluating the following variables: number of shoots in the aerial part; number of flowers; crown diameter; circumference of the cladode; number of fruits and the variation in the amount of light reaching the plants. It was observed that the plants that were outside the eucalyptus forest showed better results. In the second experiment, the allelopathic action of different concentrations of aqueous extracts of eucalyptus leaves on the germination of pitaia seeds was evaluated. This experiment was carried out in DIC with four repetitions of 60 pitaia seeds. These seeds were then subjected to treatments with different dilutions, varying from 0% (control), 12.5%, 25% and 50% of the stock solution. It was observed that as the leaf extract concentrations increased, germination decreased. The concentrations of 0% (control) and 12.5% ​​showed better results. In conclusion, in fact, eucalyptus exerted an allelopathic action on pitaia plants.